HIV/AIDS Cases in Nabire Regency, Papua: Identification of Trends and Risk Factors in 2021 - Wika Purnama Syair; Shinta Dwi Aryanti (Journal of Epidemiology and Health Science, 2025)
Background: The HIV/AIDS epidemic in Nabire Regency has escalated significantly, making it the region with the highest number of cases in Papua Province. Women of childbearing age are disproportionately affected due to socio-cultural vulnerabilities and limited access to information and healthcare. Most patients are in their productive years, possess low educational attainment, are married, and contract the disease primarily through unprotected heterosexual intercourse. Contributing factors include inadequate healthcare services, low awareness, strong social stigma, poor adherence to antiretroviral (ARV) therapy, and high prevalence of comorbidities such as tuberculosis (TB) and hepatitis B. Culture-based strategies, targeted education, and expanded health service coverage are essential to control the epidemic. Objective: This study aims to analyze HIV/AIDS cases in Nabire Regency, focusing on identifying high-risk groups and determining factors influencing incidence. Methods: A quantitative descriptive approach was applied to examine demographic characteristics and temporal trends of HIV/AIDS cases in Nabire Regency using secondary data from 2018–2022. Results: The majority of patients were women (65.6%), under 45 years old (74.4%), with low education (55.5%), employed (67.8%), married (64.4%), and of Papuan ethnicity (88.9%). Heterosexual transmission accounted for 95.6% of cases. Case numbers increased from 7,291 in 2018 to 9,073 in 2022, reflecting continued transmission and improved case detection. Conclusion: The rising HIV/AIDS trend in Nabire Regency is driven by unprotected heterosexual intercourse, compounded by socio-cultural barriers and limited services. Comprehensive, culturally sensitive interventions and improved healthcare access are urgently required. Keywords: HIV/AIDS, Nabire Regency, Papua, epidemic, women, heterosexual transmission, Indonesia